Anemia Incidence in Adolescent Girls - Yaumil Fauziah; Nukhbatul Bidayati Haka; Mega Octamelia (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Anemia in adolescent girls is a major public health problem that can persist into adulthood and contribute to increased maternal mortality, prematurity, low birth weight, and perinatal death. Data from the Padang City Health Office reported that the prevalence of anemia among adolescent girls at vocational high schools (SMKN) reached 37.5%. This study aimed to identify risk factors associated with anemia among adolescent girls at SMKN in 2019. A case–control study was conducted from January to March 2019 involving female students in grades X and XI. The sample consisted of 32 anemia cases and 32 non-anemia controls. Hemoglobin levels were measured using the Easy Touch GCHb device. Dietary intake of protein, vitamin C, and iron was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQFFQ), while infectious diseases were identified through questionnaires. Data were analyzed using univariate analysis and bivariate analysis with Chi-square tests and Odds Ratios. The results showed that protein intake (p = 0.00; OR = 7.667), vitamin C intake (p = 0.00; OR = 5.000), and infectious diseases (p = 0.01; OR = 3.571) were significantly associated with anemia. Iron intake was not identified as a significant risk factor (p = 0.64; OR = 1.552). In conclusion, anemia prevalence among adolescent girls at SMK Negeri 03 Padang remains high. Efforts to improve nutritional intake, particularly protein, vitamin C, and iron, are strongly recommended to reduce anemia risk and improve adolescent health outcomes.